Diagnostic accuracy of machine learning for endometriosis: a systematic review and meta-analysis - Zhang, Bingyi; Lv, Xiaoli; Li, Dan; Zhang, Longtao; Ru, Ziyang; Ma, Yuxia (Frontiers in Endocrinology, 2026)
BackgroundResearchers have explored machine learning (ML) in diagnosing endometriosis. However, systematic evidence on its diagnostic accuracy for endometriosis remains scarce.ObjectiveTo systematically review the performance of machine learning for the diagnosis of endometriosis.Search strategyPubMed, Embase, Cochrane Library, and Web of Science were systematically searched up to October 11, 2024.Selection criteriaStudies that constructed machine learning models to diagnose endometriosis.Data collection and analysisTwo reviewers independently screened studies, extracted data, and assessed study quality. The risk of bias of the included studies was assessed using the Prediction Model Bias Risk Assessment Tool.Main resultsA total of 45 publications were included. Participant numbers ranged from 39 to 612,777. A meta-analysis showed that the area under the curve (AUC), sensitivity, and specificity of models based on clinical features were 0.810 (95% confidence interval [CI]: 0.786–0.835), 0.81 (95% CI: 0.77–0.84), and 0.76 (95% CI: 0.73–0.79) in the training sets, and 0.796 (95% CI: 0.770–0.822), 0.80 (95% CI: 0.75–0.84), and 0.76 (95% CI: 0.72–0.80) in the validation sets. The AUC, sensitivity, and specificity of models based on genetic information were 0.982 (95% CI: 0.975–0.990), 0.94 (95% CI: 0.90–0.97), and 0.99 (95% CI: 0.94–1.00) in the training sets. For the validation sets, these metrics were 0.865 (95% CI: 0.701–1.000), 0.83, and 0.59–0.96. Models based on imaging features exhibited an AUC of 0.979 (95% CI: 0.959–0.999) and 0.983 (0.971–0.995) in the training and validation sets, respectively.ConclusionsML models, particularly those based on genetic information and imaging, possess substantial accuracy for detecting endometriosis.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024605113.